2011
DOI: 10.1007/s11434-011-4460-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic consequences of postglacial colonization by the endemic Yarkand hare (Lepus yarkandensis) of the arid Tarim Basin

Abstract: Orogenesis of the Qinghai-Tibetan Plateau, which occurred in a stepwise manner, contributed to the extreme aridity of the Tarim Basin, resulting in vulnerable and unstable ecosystems. Quaternary climatic oscillations may have affected the ecosystems and, consequently, the distributions and genetic structuring of the Tarim Basin's biota. We used nucleotide sequence data from 2 mitochondrial (mt) DNA genes (Cyt b and the D-loop) to test hypotheses associated with the matrilineal and demographical histories of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 72 publications
5
27
1
Order By: Relevance
“…Diversification within the C. hanglu sublineage may have occurred due to glacial fragmentation and subsequent recolonization events in the early/middle Pleistocene, similarly to other species that currently live around the Basin, for example the Yarkand hare Lepus yarkandensis (Shan et al. ), and Agamid lizard Phrynocephalus axillaris (Zhang et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversification within the C. hanglu sublineage may have occurred due to glacial fragmentation and subsequent recolonization events in the early/middle Pleistocene, similarly to other species that currently live around the Basin, for example the Yarkand hare Lepus yarkandensis (Shan et al. ), and Agamid lizard Phrynocephalus axillaris (Zhang et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The second sublineage, C. hanglu, after a short migration eastward, remained isolated west of the Tarim Basin, unable to cross the Taklimakan desert, and/or the Pamir Plateau, Tian Shan and Kunlum Mountains, that surrounded the Basin with peaks exceeding 7000 m a.s.l., after completion of their orogeny during middle Miocene times (Yang et al 2014). Diversification within the C. hanglu sublineage may have occurred due to glacial fragmentation and subsequent recolonization events in the early/middle Pleistocene, similarly to other species that currently live around the Basin, for example the Yarkand hare Lepus yarkandensis (Shan et al 2011), and Agamid lizard Phrynocephalus axillaris (Zhang et al 2010). In contrast to our reconstruction, previous morphology-based analyses suggested that C. hanglu red deer would derive from C. elaphus populations dispersing eastward through the Middle East during the middle Pleistocene (cf.…”
Section: Biogeography and Evolutionary Patternsmentioning
confidence: 99%
“…Even in the Tarim Basin, which was barely inhabitable due to the particularly dry and cold climate, a LGM refugium for the Yarkand hare ( Lepus yarkandensis ) has recently been identified on the its south‐western margin of the basin. This species of hare lived through that period mainly by using meltwater from glaciers in the Tishan and Kunlun Mountains (Shan et al ., ). On the basis of these collective results, we argue that the prevailing view that most extant species in the central and western regions of QTP occupy their current ranges through post‐glacial recolonization from eastern refugia requires further verification, at least for small mammals.…”
Section: Discussionmentioning
confidence: 97%
“…a). Furthermore, there is growing evidence showing that multiple refugia of a variety of organisms were widespread in QTP during LGM and earlier glaciations, including in the central (Wang et al ., ), north‐western (Shan et al ., ) and south‐western regions (Hofmann, ). For small mammals, Tang et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation